Forward-Looking Labor Supply Responses to Changes in Pension Wealth: Evidence from Germany - Elisabeth Artmann; Nicola Fuchs-Schündeln; Giulia Giupponi (Institute of Labor Economics (IZA), 2023)
We provide new evidence of forward-looking labor supply responses to changes in pension wealth. We exploit a 2014 German reform that increased pension wealth for mothers by an average of 4.4% per child born before January 1, 1992. Using administrative data on the universe of working histories, we implement a difference-in-differences design comparing women who had their first child before versus after January 1, 1992. We document significant reductions in labor earnings, driven by intensive margin responses. Our estimates imply that, on average, an extra euro of pension wealth in a given period reduces unconditional labor earnings by 54 cents.
Keywords: H55; J22; J26; 330; labor supply; social security; pension wealth